Islamic Legal Perspectives on the Viral Behavior Phenomenon Among Teenagers - Muh. Evendi; Ahmad Jalaludin (International Research and Development for Human Beings (IRDH), 2025)
The phenomenon of viral behavior among teenagers has become a rapidly growing social symptom in line with the development of digital technology and social media. This study aims to analyze viral behavior from the perspective of Islamic law, by examining the boundaries of ethics, sharia, and its social implications. The method used is a literature review with a normative approach, focusing on the Qur’an, Hadith, and the views of scholars. The results show that viral phenomena are not always negative but can become ongoing good deeds if directed toward virtue. Conversely, viral behavior that contains slander, gossip, pornography, or useless acts is considered an ongoing sin with harmful implications for both individuals and society. The conclusion is that Islamic law encourages Muslims, especially teenagers, to use social media wisely and maintain behavior in accordance with the principle of enjoining good and forbidding evil.